The Nexus between Stakeholder Pressure and Green Innovation Practices - Sharifah Sabrina, Syed Ali; Mohd Rizal, Yaakop; Nur Zaimah, Ubaidillah; Salawati, Sahari; Mohd Waliuddin, Mohd Razali (2022)
Green innovation practices have arisen as a sustainable business strategy in corporations worldwide due to environmental degradation. The shift toward green innovation (GI) is being driven by corporations' environmental concerns and the concern over sustainability is more than ever especially in the manufacturing industry. Knowing stakeholders and their concerns is critical for organisations to incorporate more ideas into sustainability practices, as such the pressure from stakeholders are the primary motivator for firms to implement green innovation. While the existing literature frequently suggests the drivers of GI, it remain inconclusive. Thus, this research intend to examine the relationship between the stakeholder pressure and green innovation practices. The primary data using questionnaire survey will be obtained from the manufacturing firms in Malaysia. Drawing upon normative stakeholder theory, this research aimed to provide empirical evidence showing that stakeholder pressure can have influence and at the same time can improve on the firm GI practices. The result of this research can deepen and will offer theoretical and practical contribution whereby of which salient stakeholders can give greater influence for organization to practice GI. The empirical confirmation through GI practices also can be vital in this century and as a primary means to achieve corporate sustainability.